2009
DOI: 10.1371/journal.pone.0004337
|View full text |Cite
|
Sign up to set email alerts
|

Confusion and Conflict in Assessing the Physical Activity Status of Middle-Aged Men

Abstract: BackgroundPhysical activity (including exercise) is prescribed for health and there are various recommendations that can be used to gauge physical activity status. The objective of the current study was to determine whether twelve commonly-used physical activity recommendations similarly classified middle-aged men as sufficiently active for general health.Methods and FindingsWe examined the commonality in the classification of physical activity status between twelve variations of physical activity recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 30 publications
3
50
0
1
Order By: Relevance
“…Contrary, in the step-based and questionnaire-based recommendation, every step or minute counts. Our results are in line with a study in healthy men, which also showed huge differences between various recommendations [34]. …”
Section: Discussionsupporting
confidence: 93%
“…Contrary, in the step-based and questionnaire-based recommendation, every step or minute counts. Our results are in line with a study in healthy men, which also showed huge differences between various recommendations [34]. …”
Section: Discussionsupporting
confidence: 93%
“…Our data and that of others 11 suggest more important levels of inactivity in these milder stages in comparison with healthy controls which is probably related to the method of measuring. 23 …”
Section: Discussionmentioning
confidence: 99%
“…This was the result of the use of different questionnaires, the lack of sufficient information for transforming the reported physical activity in values with similar units (eg, METs), and untraditional ways to report physical activity compared with the specific literature. Therefore, future studies should try to standardize how physical activity results from questionnaires and motion sensors are reported, possibly following more common procedures so comparisons with the literature will be easier (Appendix) [5,48,67]. The only possible comparisons were with the amount of steps determined using pedometers (10,000 steps target) and with the data recently reported in a meta-analysis performed on studies examining physical activity in healthy people.…”
Section: Discussionmentioning
confidence: 99%